Determining Factors Affecting Agricultural Credit Demand: A Research in Erzurum Province, Türkiye - Yusuf Akan; Ayhan Korkulu (Journal of Agricultural Sciences)
The purpose of this research is to identify the variables that might influence the demand for low-interest business and investment loans given to Türkiye livestock and agricultural industries. A face-to-face survey of 384 producers who go on with their production operations in ten distinct Erzurum districts provided the data utilized in the study. Binary logistic regression analysis was used to identify the factors influencing credit use. The data shows that producers in the age groups of 20–30 are less likely to utilize credit than those in the 31–45 and 46–60 age groups. Credit use is higher among individuals involved in mixed production activities than in crop production only. Individuals who report being in excellent health have a higher likelihood of using credit than those who report being in bad health. Having a house of one's own increases the likelihood of using credit. Those whose production activity location is close to the district center are more likely to use credit. It has been shown that people are more likely to utilize if they say the guarantees that loan providers want are inexpensive, if they say they will carry on with their production, and if they say they are happy with the amount of expertise needed for production.